Using spatial cross-correlation image analysis to characterize the influence of strain rate on plastic damage in molecular dynamics simulations. (12th September 2017) - Li, D; Reich, B J; Brenner, D W
Abstract: We demonstrate how spatial cross-correlation image analysis can be used to characterize the strain rate dependence of simulated plastic damage for three systems, two copper bi-crystals containing complementary tilt grain boundaries, and a copper crystal without a grain boundary strained along the [011] direction. Distributions of cross-correlation coefficients (CCs) generated within the same system and strain rate are used to characterize the range of different types of damage observed, while CC distributions generated between the same system but at different strain rates indicate the degree of similarity of the damage generated between strain rates. For both bi-crystals, the CC distributions indicate a broader range of damage configurations as strain rate decreased. For a 15° tilt angle CC distributions generated between the damage configurations at the highest and the lowest strain rates indicate a common set of damage configurations, while for the 45° tilt angle the same analysis suggested comparatively fewer similar damage configurations. In contrast, lower strain rates for the system without initial grain boundaries resulted in far fewer distinct damage configurations and a high degree of matching between the similar configurations. In this case the damage is composed of ordered stacking faults along the (111) planes.